2006
DOI: 10.1097/01.bto.0000252134.08424.44
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Transposition of the Ulnar Nerve in the Athletic Elbow

Abstract: Ulnar neuritis at the elbow is a well described and relatively common entity among compression neuropathies of the upper extremities, especially in the athletic population. Ulnar neuritis in the throwing athlete may occur secondary to traction from valgus stress, compression from adhesions, osteophytes, flexor muscle hypertrophy, or friction because of subluxation of the nerve. Different operative techniques to treat recalcitrant cases have been described in the literature. These include decompression in situ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…However, Macadam et al 20 found a trend towards a better clinical outcome in patients treated with anterior transposition as opposed to simple decompression, requiring prospective studies and additional randomized trials using objective measures to provide statistical support for this finding. Similarly of what has been published in the literature, 6 , 21 we obtained high rates of success and satisfaction with the subcutaneous transposition technique.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, Macadam et al 20 found a trend towards a better clinical outcome in patients treated with anterior transposition as opposed to simple decompression, requiring prospective studies and additional randomized trials using objective measures to provide statistical support for this finding. Similarly of what has been published in the literature, 6 , 21 we obtained high rates of success and satisfaction with the subcutaneous transposition technique.…”
Section: Discussionsupporting
confidence: 81%
“…Surgery is indicated in cases of failure of conservative treatment, or in patients with severe symptoms or muscle atrophy. There are several different techniques, such as isolated decompression, 5 decompression with anterior transposition, 6 - 8 medial epicondylectomy, 9 - 11 and endoscopic decompression, 12 - 14 but there is no consensus on which technique is best. 15 …”
Section: Introductionmentioning
confidence: 99%
“…There are multiple surgical techniques currently recommended for the treatment of CTS (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) , though considerable controversy remains in the literature regarding the best surgical strategy for this compressive neuropathy. Most comparative studies demonstrate similar results and no particular technique has been demonstrated to be associated with statistical differences among the results obtained (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no consensus on the ideal surgical technique for the treatment of CTS. Several techniques have been described over the years, including simple decompression (4) , anterior transposition (subcutaneous, intramuscular, or submuscular) 5 , 6 , 7 , medial epicondylectomy 8 , 9 , 10 and in situ endoscopic decompression 11 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%